Analysis the Impact of Renewable Energy on Work Needs Mediating the Welfare of Fishermen in Aceh Besar - Yeni, Manovri; Murni, Murni; Usman, Musliadi Bin (Formosa Journal of Multidisciplinary Research, 2024)
Fishermen's welfare is a critical issue in economic and social development, especially in coastal areas like Aceh Besar. The implementation of renewable energy not only impacts cost reduction but also addresses fishermen's work needs. Through renewable energy technology adoption, fishermen can enhance productivity with more efficient fishing gear and longer operational durations without returning to land for refueling. This study employs Partial Least Squares (PLS) structural equation modeling to investigate the intricate relationships among Economic Growth (EG), Fishermen's Work Needs (FWN), Use of Renewable Energy (USE), and Welfare of Society (WS). The analysis reveals that Economic Growth significantly enhances Fishermen's Work Needs), indicating that economic improvements drive increased demands and requirements in the fishing sector. Although Economic Growth positively influences Welfare of Society, this relationship lacks statistical significance, suggesting a moderate effect. Conversely, the Use of Renewable Energy positively impacts both Fishermen's Work Needs, and significantly enhances Welfare of Society, the minimal influence of Fishermen's Work Needs on Welfare of Society. underscores the limited direct effect of sector-specific needs on broader societal outcomes. These findings provide critical insights for policymakers and stakeholders in developing sustainable development strategies that balance economic growth, renewable energy adoption, and societal welfare.